Empowering MSMEs Through Financial Literacy and Management Skills - Yuni Sara (Proceeding of The International Conference on Economics and Business, 2022)
This research aims to investigate strategies for enhancing financial literacy and management skills among Micro, Small, and Medium Enterprises (MSMEs). The study utilizes a mixed-method approach incorporating interviews, surveys, and case studies to explore the current financial literacy levels among MSME owners, identify effective training models, and assess the impact of such interventions on business performance. Sampling techniques involve purposive sampling of MSMEs across diverse sectors and geographical locations. Data analysis employs thematic analysis to extract patterns and themes from qualitative data, complemented by statistical techniques for quantitative data. Preliminary findings underscore the significance of tailored financial education programs, interactive workshops, and mentorship schemes in augmenting MSMEs' financial competencies. The research contributes to the discourse on empowering MSMEs through targeted interventions, shedding light on effective strategies to unlock their potential for sustainable growth and economic development.